Understanding light in lightweight fabric (ETFE foil) structures through field studies - Lau, Benson; Aziz Masih, Dawa Azad; Ademakinwa, Abdulquadri Adesoji; Low, Siew Woon; Chilton, John (Elsevier, 2016)
This paper presents an experimental approach to investigate the luminous environment in lightweight fabric structures through field study. Buildings selected for the field study included the Engineering Science Learning Centre at the University of Nottingham and the Clarke Quay in Singapore. By undertaking on site monitoring under different sky conditions in the chosen buildings with distinctively different site context, this research project explores how the typical homogeneously lit and rather dull luminous environment in lightweight fabric structure can be improved for enhanced visual interest, visual comfort, and three-dimensional modelling under both sunny and overcast sky conditions. Research data obtained from the subjective appreciation of the internal luminous environments and the quantitative spot measurement and mapping of light are compared and discussed. This study concluded that selective use of transparent and translucent components in the ETFE envelope can offer architectural designers the opportunities to create well balanced, yet dynamic lit scenes. Also by combining single skin ETFE foil and the double or triple layered ETFE cushion and introducing ETFE cushions with different light transmittance to the building envelope can help improve the overall visual and luminous environment and enhance task illumination. The key findings from this research work are applicable to the design of light in lightweight fabric structure in general.